2021
DOI: 10.3390/antibiotics10050569
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazinium Photosensitizers Associated with Silver Nanoparticles in Enhancement of Antimicrobial Photodynamic Therapy

Abstract: Antimicrobial photodynamic therapy (APDT) and silver nanoparticles (AgNPs) are known as promising alternatives for the control of microorganisms. This study aims to evaluate the antifungal activity of APDT, particularly by using the association of low concentrations of phenothiazinium photosensitizers (PS) methylene blue (MB), new methylene blue N (NMBN), and new methylene blue N Zinc (NMBN-Zn) in association with biosynthesized AgNPs. The AgNPs were characterized by UV-Vis spectrophotometry, transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“… 17 , 36 Therefore, the ζ changes observed for the systems containing ZnPs suggest that an interaction between the cationic porphyrins and AgNPs is taking place in all conditions tested. A similar behavior was observed by Rigotto-Caruso et al, 10 who reported a reduction of the ζ absolute value of AgNPs due to the presence of cationic phenothiazines. Likewise, Rodrigues et al 9 also observed a reduction in the ζ modulus when Ag nanoprisms were associated with the cationic dye methylene blue.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“… 17 , 36 Therefore, the ζ changes observed for the systems containing ZnPs suggest that an interaction between the cationic porphyrins and AgNPs is taking place in all conditions tested. A similar behavior was observed by Rigotto-Caruso et al, 10 who reported a reduction of the ζ absolute value of AgNPs due to the presence of cationic phenothiazines. Likewise, Rodrigues et al 9 also observed a reduction in the ζ modulus when Ag nanoprisms were associated with the cationic dye methylene blue.…”
Section: Resultssupporting
confidence: 87%
“…1 log 10 inactivation of yeasts. Similarly, Rigotto-Caruso et al 10 found that biosynthesized spherical AgNPs did not show great effects in inhibiting the growth of C. albicans (ATCC 64548), with or without irradiation by a red LED (635 nm, PIT of 30 min, IR time of 16.41 min, and 15 J/cm 2 ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Rigotto Caruso et al (2021) evaluated the antifungal activity of aPDT in vitro with different phenothiazinium PSs (methylene blue, new methylene blue N, and new methylene blue N Zinc) in combination with biosynthesized silver nanoparticles. The toxicity of all the tested compounds during their study was verified in the G. mellonella model [ 225 ]. The tests performed in a study by Malacarne et al (2023) evaluated the toxicity of porphyrin PS on G. mellonella larvae and its cytotoxicity on hemocytes.…”
Section: Principles Of Apdt and The Use Of G Mellonella ...mentioning
confidence: 99%